2014
DOI: 10.1007/s13277-014-2567-8
|View full text |Cite
|
Sign up to set email alerts
|

MT1-MMP is not a good prognosticator of cancer survival: evidence from 11 studies

Abstract: MT1-MMP exhibits diverse expressions in patients with cancer and could be considered as potential prognostic biomarker of cancer. We performed a meta-analysis aiming to provide more sufficient evidence that MT1-MMP expression is associated with poor overall survival in several types of cancers. We systematically searched the studies from databases and carefully identified based on eligibility criteria. The association between MT1-MMP expression and overall survival in cancers was estimated using Review Manager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 37 publications
(54 reference statements)
1
17
0
Order By: Relevance
“…We found that high expression of MMP-14 may be an independent poor prognostic factor (OS, HR = 1.98, 95% Cl: 1.76-2.22, P < 0.001 and DFS/PFS, HR = 3.61, 95% Cl: 2.39-5.43, P < 0.001), particularly in multivariate analysis group (HR = 2.64, 95% CI: 1.95-3.58, P < 0.001), and patients with gastric cancer (HR = 2.21, 95% CI: 1.76-2.77, P < 0.001) and HCC (HR = 2.14, 95% CI: 1.35-2.19, P < 0.001) and oral cancer(HR = 1.69, 95% CI: 1.30-3.20, P < 0.001). Our findings of gastric cancer were consistent with another similar study [64], nevertheless, no correlation was observed between the MMP-14 expression and the prognosis of colorectal cancer.…”
Section: Discussionsupporting
confidence: 92%
“…We found that high expression of MMP-14 may be an independent poor prognostic factor (OS, HR = 1.98, 95% Cl: 1.76-2.22, P < 0.001 and DFS/PFS, HR = 3.61, 95% Cl: 2.39-5.43, P < 0.001), particularly in multivariate analysis group (HR = 2.64, 95% CI: 1.95-3.58, P < 0.001), and patients with gastric cancer (HR = 2.21, 95% CI: 1.76-2.77, P < 0.001) and HCC (HR = 2.14, 95% CI: 1.35-2.19, P < 0.001) and oral cancer(HR = 1.69, 95% CI: 1.30-3.20, P < 0.001). Our findings of gastric cancer were consistent with another similar study [64], nevertheless, no correlation was observed between the MMP-14 expression and the prognosis of colorectal cancer.…”
Section: Discussionsupporting
confidence: 92%
“…MMPs have been identified as up-regulated in GC, either tissues or cell lines, and have also been associated with clinicopathologic features and/or survival including MMP 3 [ 168 ], 7 [ 168 – 170 ], 11 [ 162 , 168 ], 9 [ 168 , 171 , 172 ], 12 [ 168 ], 21 [ 168 , 173 ], MT1 [ 174 176 ], 14 [ 177 ], 1 [ 162 ], 2 [ 162 ], and 28 [ 162 ].…”
Section: Emerging Markersmentioning
confidence: 99%
“…Membrane type 1-Matrix Metalloproteinase (MT1-MMP, also known as MMP14) has emerged as an attractive biomarker for tumor-targeted antibody development since this protein is crucial for the progression, invasion, migration and angiogenesis of tumors[ 12 , 13 ]; and specifically, its expression correlates with tumor grade and it is associated with reduced survival in gliomas[ 14 , 15 ] and other cancers[ 16 ]. In addition, a growing body of evidence reveals that overexpression of MT1-MMP plays also a significant role in promoting gliomagenesis[ 17 ].…”
Section: Introductionmentioning
confidence: 99%